TESA-blot for the diagnosis of Chagas disease in dogs from co-endemic regions for Trypanosoma cruzi, Trypanosoma evansi and Leishmania chagasi - Umezawa, E. S.; Souza, A. I.; Pinedo-Cancino, V. [UNESP]; Marcondes, M. [UNESP]; Marcili, A.; Camargo, L. M. A.; Camacho, Aparecido Antonio [UNESP]; Stolf, A. M. S.; Teixeira, M. M. G. (Elsevier B.V., 2009)
We standardized serodiagnosis of dogs infected with Trypanosoma cruzi using TESA (trypomastigote excreted-secreted antigen)-blot developed for human Chagas disease. TESA-blot showed 100% sensitivity and specificity. In contrast, ELISA using TESA (TESA-ELISA) or epimastigotes (epi-ELISA) as antigen yielded 100% sensitivity but specificity of 94.1% and 49.4%, respectively. When used in field studies in an endemic region for Chagas disease, visceral leishmaniasis and Trypanosoma evansi (Mato Grosso do Sul state, Central Brazil), positivities were 9.3% for TESA-blot, 10.7% for TESA-ELISA and 32% for epi-ELISA. Dogs from a non-endemic region for these infections (Rondonia state, western Amazonia) where T cruzi is enzootic showed positivity of 4.5% for TESA-blot and epi-ELISA and 6.8% for TESA-ELISA. Sera from urban dogs from Santos, São Paulo, where these diseases are absent, yielded negative results. TESA-blot was the only method that distinguished dogs infected with T cruzi from those infected with Leishmania chagasi and/or Trypanosoma evansi. (C) 2009 Published by Elsevier B.V.
Keywords: Trypanosoma cruzi; Canine Chagas disease; TESA-blot; serological diagnosis; Dog; Leishmania chagasi; Trypanosoma evansi